Islamic Banking Financial Institutions Analysis of Growth and Development in Indonesia - Sofyan Abas (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The issuance of the Financial Services Authority Regulation (POJK) number 12 of 2023 can actually require Conventional Commercial Banks in Indonesia to separate their Sharia Business Units (UUS) if they have met the conditions set out in POJK number 12 of 2023. This study aims to analyze the acceleration or development and development of Islamic banking financial institutions in Indonesia. The type of this research is qualitative research with secondary data analysis presented descriptively. This research was conducted by means of a literature study or literature review taken from various existing sources in the form of data or documents, namely through financial reports of Islamic banks, books, international and national scientific journals, magazines, scientific papers, articles, the internet, national newspapers, archives, laws, Bank Indonesia (BI) regulations, Financial Services Authority (OJK) regulations and all forms of government regulations relating to Islamic banking in Indonesia. Furthermore, the results of the study can show that the acceleration, growth and development of financial institutions in the Islamic banking sector in the country is growing significantly, this is evidenced by several conventional banks that have metamorphosed into Islamic Commercial Banks. In the performance report of the Financial Services Authority that there are 14 banks in Indonesia at the end of 2024 have become Islamic Commercial Banks or BUSs.